Cancer astrocytes have a more conserved molecular status in long recurrence free survival (RFS) IDH1 wild-type glioblastoma patients: new emerging cancer players - Franceschi, Sara (Oncotarget, 2018)
Glioblastoma is a devastating disease that despite all the information gathered so far, its optimal management remains elusive due to the absence of validated targets from clinical studies. A better clarification of the molecular mechanisms is needed. In this study, having access to IDH1 wild-type glioblastoma of patients with exceptionally long recurrence free survival (RFS), we decided to compare their mutational and gene expression profile to groups of IDH1 wild-type glioblastoma of patients with shorter RFS, by using NGS technology. The exome analysis revealed that Long-RFS tumors have a lower mutational rate compared to the other groups. A total of 158 genes were found differentially expressed among the groups, 112 of which distinguished the two RFS extreme groups. Overall, the exome data suggests that shorter RFS tumors could be, chronologically, in a more advanced state in the muli-step tumor process of sequential accumulation of mutations. New players in this kind of cancer emerge from the analysis, confirmed at the RNA/DNA level, identifying, therefore, possible oncodrivers or tumor suppressor genes.